An analytical study of initial subduction of the plate based on a bibliometric analysis method spanning 1995–2024 - Zhang, Yongqiang; Jiang, Nan; Liu, Kexin (Frontiers in Earth Science, 2025)
Subduction zones constitute a fundamental element of plate tectonic theory, with the initial subduction phase representing a critical but poorly constrained transitional stage in the development of mature subduction systems. Using CiteSpace and VOSviewer knowledge mapping tools, we conducted a systematic bibliometric analysis of 6,728 peer-reviewed publications (1995–2024) to assess recent advancements in initial subduction research. This investigation reveals distinct patterns in authorship, geographical distribution, institutional productivity, and evolving research priorities within initial subduction studies. Four principal investigators emerge as dominant contributors through seminal publications: Robert J. Stern (University of Texas) established foundational models for slab dehydration processes, Julian A. Pearce (Cardiff University) pioneered geochemical discriminants of subduction-related magmatism, Sun S. Shen (Chinese Academy of Sciences) advanced isotopic tracing methodologies for mantle wedge processes, and Yildirim Dilek (Miami University) redefined ophiolite classification frameworks in subduction initiation contexts. Geographically, Chinese researchers lead in publication output (28% of total studies). Institutional productivity analysis identifies the Chinese Academy of Geological Sciences as the predominant contributor (313 publications, centrality = 0.53). Four journals dominate disciplinary discourse: EARTH PLANET SC LETT (1,942 relevant publications) leads in high-resolution geochemical studies, followed by Geology (1,792) focusing on field-based tectonic reconstructions, Tectonophysics (1,696) specializing in geodynamic modeling, and J GEOPHYS RES-SOL EA (1,552) publishing numerical simulations of slab nucleation. Current research converges on two primary domains: (1) characterization of proto-subduction signatures through forearc basalts, suprasubduction zone ophiolites, and metamorphic sole assemblages, and (2) mechanical modeling of spontaneous versus induced subduction initiation mechanisms. Emerging methodologies integrate high-precision zircon geochronology (±0.1 Myr resolution), multi-isotopic (B-Li-Sr-Nd) tracer systems, and 3D numerical simulations using platforms like ASPECT and Underworld.